2019
DOI: 10.7717/peerj.8029
|View full text |Cite
|
Sign up to set email alerts
|

Risk-taking behavior, the second-to-fourth digit ratio and psychological features in a sample of cavers

Abstract: BackgroundThe risk-taking behavior is largely modulated by the subject’s history, its lifestyles, by the characteristics of the situations with which it is compared, and also by the effects of prenatal androgens. Thus, the personality of the single person is a significant predictor of such way of acting.MethodsThe present study aimed to explore the relationship between Digit Ratio Measurement (2D:4D) and personality factors capable to be good predictors for choosing highly risky activities, such as caving. Fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 44 publications
2
8
1
Order By: Relevance
“…Therefore, our results indicate that lower 2D:4D is associated with lower emotional stability (higher neuroticism) in women, and consequently we presume that is also associated with higher prenatal testosterone exposure. These results are partially in disagreement with previous studies which found a relationship between 2D:4D and the neuroticism-emotional stability dimension but seem to be in the PLOS ONE opposite direction [28,29,35,[39][40][41][42]; or, conversely, have found no relationship between these variables [30][31][32][33][36][37][38]. In most of the previous studies neuroticism was measured through the Neo Five-Factor Inventory, and here we measured emotional stability through the BFQ.…”
Section: D:4d Is Positively Related To Emotional Stability But Not Wcontrasting
confidence: 99%
See 3 more Smart Citations
“…Therefore, our results indicate that lower 2D:4D is associated with lower emotional stability (higher neuroticism) in women, and consequently we presume that is also associated with higher prenatal testosterone exposure. These results are partially in disagreement with previous studies which found a relationship between 2D:4D and the neuroticism-emotional stability dimension but seem to be in the PLOS ONE opposite direction [28,29,35,[39][40][41][42]; or, conversely, have found no relationship between these variables [30][31][32][33][36][37][38]. In most of the previous studies neuroticism was measured through the Neo Five-Factor Inventory, and here we measured emotional stability through the BFQ.…”
Section: D:4d Is Positively Related To Emotional Stability But Not Wcontrasting
confidence: 99%
“…On the other hand, although we did not find any significant association between 2D:4D and the other four dimensions and these results agree with several previous investigations, other studies have shown controversial results. For example, referring to agreeableness, some studies, like ours, have not found a significant association with 2D:4D [29,30,37,42], others have found a positive correlation [31,32,36] and others a negative correlation [28,33]. This inconsistency is another example that more research is needed in this field.…”
Section: Plos Onementioning
confidence: 55%
See 2 more Smart Citations
“…Notably, the multivariate approach used provided a single dependent variable and multiple independent features. Finally, a Receiver Operating Characteristic (ROC) ( Zweig & Campbell, 1993 ) analysis was performed to test the capability of the predicted SA form PPG features to discriminate high contingent SA as described by the State-Trait Anxiety Inventory (STAI-Y) (threshold = 40) ( Rinella et al, 2019 ). It is worth to notice, that the novelty of this work does not rely on the specific statistical algorithm used (i.e., multivariate regression), but it is based on the employment of a multivariate algorithm for prediction of SA from several PPG features in a machine learning framework, which is a general field of applied statistics that uses multivariate approaches for prediction purposes ( Michie, Spiegelhalter & Taylor, 1994 ).…”
Section: Introductionmentioning
confidence: 99%